Science as a matter of state: imperialism and scientific missions in central Brazil - Xavier, Glauber Lopes; Marques Cardoso, Pedro Henrique (Revista Territórios e Fronteiras, 2024)
This paper analyzes the scientific research organized by the Central Brazil Foundation (FBC) in partnership with international research institutions in Central Brazil. Much of this research was configured as an important scientific endeavor aimed at discovering the natural potential of the territory. Therefore, the objective was to analyze the imperialist policy contained in these studies and research conducted by these institutions, understanding that such research had not only the purpose of covering issues related to knowledge itself but also the objective of serving as an instrument of domination in the framework of peripheral and dependent capitalism.